KONSTRUOWANIE TOŻSAMOŚCI – CZYNNIKI SPOŁECZNO-KULTUROWE - Golka, Marian (Wydział Prawa i Administracji UAM, 2012)
We współczesnym świecie tożsamości ludzi nie są gotowe, lecz są w dużym stopniu konstruowane przez jednostki i grupy w procesie życia społeczno-kulturowego. Praktycznie wszystkie przejawy tego życia – postrzeganie własnych cech fizycznych, psychicznych i społecznych wraz z autorefleksją nad nimi, kontakty z innymi ludźmi, pamięć społeczna, władza, kultura masowa – mogą oddziaływać w procesie konstruowania tożsamości. Artykuł poświęcony jest wyodrębnieniu i scharakteryzowaniu tych czynników biorących udział w konstruowaniu tożsamości.

*Identities in the contemporary world are not ready-made but are to a large extent constructed by individuals and groups of individuals in the process of social and cultural life. Practically all aspects of that life – perceived as own physical, mental, and social features – followed by autoreflection on them, as well as contacts with other people, social memory, power, or mass culture, may influence the process in which identity is being created. The paper focuses on separation and characterisation of factors that play a role in identity construction.
CONSTRUCTING IDENTITY – SOCIAL AND CULTURAL FACTORS
Keywords: tożsamość; identity; społeczeństwo; society; kultura; culture; konstruowanie; constructing